Program pliometric excirses for to improve to the jump in the lounchwoman of softball in young category (Revista científica Olimpia, 2016)
This investigation has as an objective to elaborate a program of pliometrics.) Exercises to improve the jump in the Softball pitchers of the juvenile category to contribute to increase the faster strength of the legs as well as to prove the practical effectiveness of these exercises. We did it with a sample of four female athletes of 16 to 17 ages who were selected because of their physical and anthropometrics conditions to make this investigation in a four weeks period of time. We used different theoretic methods such as analytic-synthetic, inductive-deductive, historical-logical, and hypothetic-deductive. Empirics: Observation, measuring, pedagogical test, and the experiment. Mathematical statistics, standard deviation and arithmetic mean. The specialists diagnosed that there are some deficiencies in the technical element and that the Integral program of the athletes training don’t have this topic. The novelty of this work is the use of long jumpers exercises applied to the softball pitchers.
Keywords: softball, fast strength of legs, program of pliometrics exercises.